Estudo fitoquímico e atividades antifúngica e antiprotozoária do óleo essencial de genótipos de erva-baleeira (Varronia curassavica Jacq.) - Nizio, Daniela Aparecida de Castro (2015)
The aim of this work was to characterize the chemical diversity of the essential oil from Varronia curassavica plants collected in Sergipe, to evaluate the effect of microwave extraction (MI) and hydrodistillation (HD) of essential oil from Varronia curassavica Jacq. on its chemical composition and antifungal activity and to evaluate the antiprotozoal activities of the essential oil and major compounds against Ichthyophthirius multifiliis, fish parasite. High chemical diversity was observed among the V. curassavica plants, which are distributed within the chemical groups, regardless of the collection site, probably due to genetic differences between plants studied. The compounds found in higher contents in the essential oils of the plants were tryciclene, camphene, E-caryophyllene, β-sesquiphelandrene, α-zingiberene, 7-cyclodecen-1-ona, 7-methyl-3-methylene-10-(1-propyl) and turmerone, which defined the formation of five groups according to the chemical composition and differentiation by means of cluster analysis. By cluster analysis, there was formation of five chemical groups. The essential oil of the plants from the clusters 2, 4 and 5 inhibited approximately 75% of the mycelial growth of Lasiodiplodia theobromae, after 96 hours of incubation. The essential oil from V. curassavica access VCUR-201 was extracted by HD and MI. To HD method were tested 3 extraction times (100, 120 and 140 minutes) and 3 volumes of water (1.0; 1.5 and 2.0 L). To MI method, 3 powers were tested (500, 600 and 700W), 3 times (20, 30 and 40 minutes) and 3 volumes of water (0, 25 and 50 mL). The optimal essential oil contents for the extraction methods were 700W for 40 min. without water (MI) (3.28%), and 120 min. with 1.0 L of water per flask (HD) (3.34%). The most abundant compounds for MI (700W for 40 min. without water) and HD (120 min. with 1.0 L of water/flask) were shyobunol (26.53 and 24.00%) and germacrene D-4-ol (3.60 and 10.23%). Micrographs of the surface of leaves, obtained by scanning electron microscopy (SEM), after essential oil extraction, showed that both extraction methods caused destruction of glandular trichomes. The essential oils (0.5%) obtained by MI2 (700W for 40 min. with 50 mL of water per sample) and HD1 (100 min. with 1.0 L of water per flask) resulted in 80.3% and 79.7% of inhibition of mycelial growth of C. musae, respectively. The essential oils from three V. curassavica access VCUR-001, VCUR-509 and VCUR-601, the majority compounds α-pinene, sabineno and the mixture E-caryophyllene more viridiflorol exhibited toxicity against I. multifiliis trophont and tomont phases. It was possible to confirm that the majority compounds tested are mainly responsible for the antiprotozoal activity displayed by the essential oils that contains them. Damage caused to the integrity of the membrane in trophonts and rupture of the cyst wall in tomonts seems to be the leading cause of death from protozoans incubated with essential oils of V. curassavica and isolated compounds. The essential oil of V. curassavica features potential for the control of phytopathogenic fungi and fish parasites. In the future it may be used in formulations for use in agriculture.